What is public relations to society? Toward an economically informed understanding of public relations - HALFF, Gregor, (Institutional Knowledge at Singapore Management University, 2015)
The notion of public relations contributing to the fabric of society is heavily contested in the public sphere and under-researched by the academy. The authors of this paper propose that the study of the relevance of public relations to society can be enlightened by turning to economics. Using information asymmetry as a framework, the argument is that public relations can be analyzed as a social institution that both helps to mitigate market imperfections and consequently increases the efficiency with which society's resources are allocated as well as the chances for more market participants to derive value out of economic transactions. (C) 2015 Elsevier Inc. All rights reserved.